Algorithmic thinking skill of prospective ICT teachers in solving mathematical task - Sari, Ariesta Kartika; Siswono, Tatag Yuli Eko; Lukito, Agung (Edelweiss Applied Science and Technology, 2025)
Algorithmic thinking is also one of the competencies we must develop in digital literacy and the ICT era. This study aims to determine the algorithmic thinking skills of prospective ICT teachers viewed from the accuracy and systematics in the steps to solve a mathematical problem. This research uses a descriptive quantitative approach, with a non-experimental design. The sampling technique was purposive sampling. The participants were 85 students of the informatics education program as prospective ICT teachers. Data analysis refers to the results and steps of task completion. Analysis of the participants’ work results provides information that their algorithmic thinking ability is not optimal. This is indicated by 67% of participants who are not accurate and not systematic in completing algebraic mathematics tasks. It means prospective ICT teachers need to improve their algorithmic thinking skills when producing solutions to solve tasks. The novelty of the research lies in the appropriate and systematic category indicators, as well as the existence of four models for solving mathematical tasks that demonstrate the participants’ algorithmic thinking skills. In the future, we should explore the components of algorithmic thinking and how to improve this skill, especially in the domains of mathematics and informatics education.